Wideband Tympanometry Findings in Healthy Neonates - Aithal, Sreedevi; Aithal, Venkatesh; Kei, Joseph; Wilson, Matthew (Journal of the American Academy of Audiology, 2022)
Objectives The objective of the present study was to describe pressurized wideband absorbance at tympanometric peak pressure (WBATPP) and 0 daPa (WBA0) in healthy Caucasian neonates.Subjects A total of 249 ears from 249 neonates who passed a test battery of 1,000-Hz tympanometry, distortion product otoacoustic emissions and automated auditory brainstem response were included in the study.Method WBATPP and WBA0 were averaged in one-third octave frequencies from 0.25 to 8 kHz. Data were statistically analyzed for effects of frequency, ear, and gender.Results Normative WBATPP and WBA0 data obtained from healthy neonates are presented. There was no significant difference between WBATPP and WBA0 at all frequencies. Both WBATPP and WBA0 demonstrated a multipeaked pattern with maxima of 0.80 and 0.72 at 1.25 to 1.5 and 6 kHz, respectively, and two minima of 0.45 and 0.49 at 0.4 to 0.5 and 4 kHz, respectively. The effects of ear and gender were not significant for both WBA measures.Conclusion Pressurized WBATPP and WBA0 data were provided for healthy Caucasian neonates. They will be useful for the assessment of middle ear function and assist in differentiating between conductive and sensorineural hearing losses in neonates.
Keywords: wideband absorbance; wideband tympanometry; neonates